The role of public relations in promoting the social responsibility of the economic sector in the eastern region (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to evaluate the role of public relations departments in the economic sectors in promoting social responsibility, as the efforts in this field are considered one of the main functions that contribute to building a positive and interactive image of companies and institutions among the internal and external public. The researcher used the survey method, content analysis tools and questionnaire to answer the problem of his research by collecting and analyzing data from a sample of 300 individuals including public relations employees and social responsibility employees in companies and institutions and members of the parent community: institutions of the economic sector in the Eastern Province. The researcher divided the study into two chapters, the first chapter was entitled: (Theoretical Framework of the Study), while the second chapter was entitled: (Methodological Procedures of the Study), and the two chapters included many topics, followed by the most important results, recommendations and conclusion, a list of sources, references, indexes and study appendices. The study came out with a set of results, including that economic institutions in the Eastern Province focus on performing public relations functions related to improving the mental image as a priority in their work. It also confirmed that the majority of economic sector institutions in the Eastern Province implement many community partnerships, but some of them are few and unsustainable, while they do not exist in a few of them. Among the results is that community work is carried out by a large percentage of public relations departments in economic institutions in the Eastern Province according to a strategy and plans prepared to enhance community partnerships. The implementation of social programs and initiatives by public relations departments in many economic institutions in the Eastern Province also contributes to the effective implementation of social programs and initiatives within the context of their tasks and functions.
Keywords: Public Relations; Social Responsibility; Communication Practices; Community Partnerships; Economic Sectors